Technological literacy in using Learning Management System among students in higher education institutions Tanzania: the case of two selected universities - Aines Rodrick Chasubuta; Placidius M. Ndibalema; Paul Loisulie (Academy of Cognitive and Natural Sciences, 2024)
This paper aims to test the predictive power of facilitative conditions and technological literacy skills in using the Learning Management System (LMS) for learning in a Tanzanian university setting. The paper adopts a quantitative approach in which data were analysed using the linear regression model after securitising for multicollinearity, linearity, normality of data, homoscedasticity, and measurement reliability. The study's findings indicate that the environmental context had more predictive power for technological literacy among students than the technological and organisational context. The paper provides insights to educational practitioners in HLIs to strengthen their systems so that the technological learning environment aligns with the student's technological literacy development needs. The findings also highlight the need for university authorities to adopt new technological innovations that could be used to enhance students' digital literacy skills development and be able to cope with 21st-century skills. By examining the level of technological literacy, the research can shed light on the potential barriers students face in using LMS and point out some areas where interventions are needed. This, in turn, can enhance educational outcomes by improving students' digital skills and their ability to engage with online learning resources.